Pahlawan: Representasi Perempuan dalam Cerita Disney Era Renaisans Pilihan - Daulay, Resneri; Ulfah, Helmatun Fauza (BASIS (Bahasa dan Sastra Inggris), 2022)
The occurrence of disparities in society with female characters, Disney stories told about the existence of heroine characters in the Disney renaissance era. Disney stories had become part of a show culture that has evolved into the reproduction of gender roles. This study was conducted to find the female representation as a heroine depicted in the Disney renaissance as well as to analyze the reasons how Disney heroines struggle in claiming their equality as a woman in their society. This study was categorized into qualitative and descriptive research methods. Furthermore, this study used the theory of the renowned feminist existentialism by Simone de Beauvoir, one of the Feminist icons and Philosophers of existentialism, with her book; The Second Sex, Beauvoir represented the section of the independent woman; a woman could choose independence, which means continuing to carry out the process toward freedom without having the insight of a predetermined goal. Therefore, this study aimed to elaborate how the female representation as the women to fight their equality to their desire for freedom. Thus, the heroine character was expected to be able to contribute to society in terms of gender awareness, including women.